Hypoglycemic and Antihyperglycemic Activities of Nine Medicinal Herbs Used as Antidiabetic in the Region of Lubumbashi (DR Congo). (20th April 2017) - Amuri, Bakari; Maseho, Mwamba; Simbi, Lumbu; Okusa, Philippe; Duez, Pierre; Byanga, Kahumba
Abstract : The aim of this study was to assess the hypoglycemic and antihyperglycemic activities of nine plants used as antidiabetic treatments in Lubumbashi and its surroundings. Those are Albizia adianthifolia, Azanza garckeana, Cassia occidentalis, Cassia sieberiana, Erythrina abyssinica, Gladiolus klattianus, Rauvolfia caffra, Strychnos spinosa, and Vitex madiensis . Aqueous extracts, obtained by decoction and maceration, were administered (500 mg/kg) per os to guinea pigs ( Cavia porcellus ), both in glucose baseline conditions and in oral glucose tolerance test (OGTT) conditions (glucose, 2 g/kg; follow‐up over 210 min). For OGTT experiments, area under the curve of blood glucose levels, maximum glucose concentration (Cmax), and time to reach Cmax (Tmax) were used to compare test groups with the control conditions (glucose group). In hypoglycemic tests, only three species induced significant ( p < 0.001) lowering of normal glycemia: A. adianthifolia (33% reduction), C. occidentalis (32%), and V. madiensis (43%); in the same conditions, the positive control glibenclamide (6 mg/kg) induced a blood glucose lowering of 55%. In OGTT conditions, all tested herbs were active, with the highest inhibition of glycemia increases for V. madiensis (62%) and A. adianthifolia (57%), compared with the hyperglycemic inhibition rate of glibenclamide (50%). Oral glucose tolerance test conditions appear as essential to detect the extracts most interesting for clinical use. These data support the use of studied plants for diabetes treatment in traditional Congolese medicine and indicate a good knowledge of tradipraticians in the field. Copyright © 2017 John Wiley & Sons, Ltd.